Ecological uncertainty and antipredator behaviour: an integrative perspective - Brown, Grant E.; Godin, Jean-Guy J. (Frontiers in Ethology, 2023)
Due to its unforgiving nature, predation pressure excerts strong selection pressure on the behaviour of prey animals. As a result, prey are forced to balance the conflicting demands of successfully detecting and avoiding predators and the need to engage in other fitness-related activities such as foraging, mating and social behaviour. Here, we provide an overview of the role that individual predator avoidance decisions plays in constraining behavioural phenotypes and how past experience with risks shapes current (and future) trade-offs, physiological and life history investments. Critically, access to reliable risk assessment information allows prey to respond to spatially and temporally variable predation risks. Uncertainty of predation risks is expected to limit the ability of prey to make short-and longer-term adjustments responses to predation threats, potentially increasing the indirect costs of predation. We describe a 'landscape of information' in which prey rely on publically available risk assessment information to reduce the uncertainty of predation risks associated with variable threats and the potential impact of natual and anthropogenic environmental factors which may limit information availability. Despite a long tradition of research into the antipredator trade-offs made by prey animals, there remain a number of important unanswered questions.